Endoscopic Muscle Repair of Right Internal Carotid Artery Rupture Following Endovascular Procedure. (3rd August 2020) - Pathak, Shravani; Spock, Todd; Gray, Mingyang; Liu, Katherine; Shrivastava, Raj; Iloreta, Alfred
Abstract : Carotid artery blowout syndrome (CBS) is a deadly complication usually linked to head and neck cancer therapy. We present a different etiology of endoscopic CBS, a complication of endovascular coiling of an intracranial aneurysm, treated with sternocleidomastoid (SCM) muscle graft packing. Case Presentation: An otherwise healthy 55‐year‐old female presented to the emergency room with right‐sided painless vision loss of 23 days. Computed tomography angiography demonstrated a right ophthalmic ICA aneurysm eroding into the right sphenoid sinus with optic nerve compression. Attempted endovascular repair of the aneurysm was complicated by ICA rupture into the sphenoid. An endovascular balloon was inflated proximal to the aneurysm to reduce hemorrhage as ENT performed an endoscopic sphenoidotomy. A hematoma was seen overlying the aneurysm in the superior lateral sphenoid sinus. Layers of SCM muscle were morselized and packed serially. Post‐repair angiography showed no further extravasation. Aggressive antiplatelet therapy was initiated. Packing was removed after 14 days. Twenty days postoperatively, the patient had profuse left‐sided epistaxis requiring a left sphenopalatine artery ligation. The patient's vision recovered. Discussion: Whereas CBS is often managed by endovascular coil embolism, in our case CBS was caused by this very treatment itself. This case shows the use of SCM muscle graft as an effective repair modality of ICA rupture due to endovascular coiling. Laryngoscope, 131:E764–E766, 2021